Analisis Metode Routing terhadap Hidrograf Banjir Sungai Way Sekampung di Way Kunyir Menggunakan HEC-HMS - Marfirah Ulfah; Dyah Indriana Kusumastuti; Dwi Joko Winarno (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
Flood events often occur in Indonesia so that quite a lot of people researched about the movement of floods and flood monitoring in the Watershed. The location of the study was carried out by the Way Sekampung river in Way Kunyir located in the Pringsewu district, Lampung province and is located downstream of the Batutegi dam. Flood tracing is intended to analyze the chances of a flood in the form of a flood hydrograph with or without using the Routing method and find out the results of some Routing methods in the watershed. The Routing method used in this study is Lag, Lag and K and Muskingum. The HEC-HMS modeling results state that peak discharge data when without Routing is greater than entering the Routing parameter. This is because entering the Routing parameter in modeling is very influential at peak times so that it affects the peak discharge at the watershed outlet. As a result of Muskingum Routing, the peak discharge is lower than before entering the flow routing, this is due to the occurrence of reservoirs along the river so that the peak discharge becomes lower than without Routing. The results of Lag Routing and Lag and K Routing are peak discharge decreased compared to before entering the Routing parameter. what should have happened to the peak discharge with Routing and without Routing remains the same, however, only peak discharge tranlations occur and there is travel time. This happens because there is no debit data at the station being reviewed so it uses rain data instead of HEC-HMS modeling.